The Relationship of depression, anxiety, and stress with self-care behaviors in women with gestational diabetes - Masoumeh Kordi; Mahsima Banaei Heravan (Mashhad University of Medical Sciences, 2020)
Background & aim: Gestational diabetes is the most common metabolic disorder in pregnancy, and lack of self-care is one of the important reasons for mortality in diabetic patients. Considering that glycemic control is controlled by physiological and psychological mechanisms, it seems that depression, anxiety, and stress could affect the performance of pregnant women towards their own self-care. This study aimed to determine the relationship of depression, anxiety, and stress with self-care behaviors in women with gestational diabetes. Methods: This descriptive correlational study was conducted on 400 females with gestational diabetes who referred to health-care centers and clinics of hospitals affiliated to Mashhad University of Medical Sciences, Mashhad, Iran, in 2015. Data were collected using a demographic questionnaire, a self-care scale retrieved from the Summary of Diabetes Self-Care Activities as well as Depression, Anxiety, and Stress Scale-21. The data were analyzed in SPSS software (version 22) through the Spearman correlation coefficient and multiple linear regression. Results: The results of the Spearman correlation coefficient revealed that depression, anxiety, and stress had no significant correlation with self-care (P>0.05). According to the linear regression model, none of the main variables under study obtained a significant level of less than 0.05; therefore, they were not considered as predictors of self-care (P>0.05). Conclusion: Since the results revealed that depression, anxiety, and stress had no correlation with self-care in females with gestational diabetes, further studies are recommended to be conducted in this regard with a larger sample size and in different settings.